A fast radio burst with frequency-dependent polarization detected during Breakthrough Listen observations. Issue 3 (8th April 2019) - Price, D C; Foster, G; Geyer, M; van Straten, W; Gajjar, V; Hellbourg, G; Karastergiou, A; Keane, E F; Siemion, A P V; Arcavi, I; Bhat, R; Caleb, M; et al.
ABSTRACT: Here, we report on the detection and verification of fast radio burst FRB 180301, which occurred on utc 2018 March 1 during the Breakthrough Listen observations with the Parkes telescope. Full-polarization voltage data of the detection were captured – a first for non-repeating FRBs – allowing for coherent de-dispersion and additional verification tests. The coherently de-dispersed dynamic spectrum of FRB 180301 shows complex, polarized frequency structure over a small fractional bandwidth. As FRB 180301 was detected close to the geosynchronous satellite band during a time of known 1–2 GHz satellite transmissions, we consider whether the burst was due to radio interference emitted or reflected from an orbiting object. Based on the pre-ponderance of our verification tests, we cannot conclusively determine FRB 180301 to be either astrophysical or anthropogenic in origin.